Kinetic analysis of liquid–solid contact electrification: Using adsorption models as mechanistic probes for hybrid EDL behavior - Chaithaweep, Kanokwan; Pharino, Utchawadee; Pongampai, Satana; Sriphan, Saichon; Charoonsuk, Thitirat; Hajra, Sugato; Vittayakorn, Wanwilai; Maluangnont, Tosapol; Vittayakorn, Naratip (My University, 2026)
Liquid–solid interfaces are central to technologies ranging from energy storage to triboelectric nanogenerators (TENGs). Whereas classical electric double layer (EDL) theory describes these interfaces mainly in terms of electrostatic ion adsorption, hybrid EDL concepts suggest that interfacial electron transfer may also contribute importantly to charge generation. However, the hybrid EDL model has so far been discussed primarily at a qualitative level or through complex theoretical and computational treatments, and a simple, experimentally accessible macroscopic kinetic handle that can discriminate, in operando, between adsorption‑dominated and ET‑influenced regimes remains lacking. By analyzing high-resolution charging dynamics over systematically varied H₂SO₄ and HNO₃ concentrations, a clear concentration-dependent kinetic transition is identified. At low ionic strengths, the charging process is described more effectively by pseudo-second-order (PSO) kinetics, consistent with a reaction-influenced interfacial step, whereas at higher concentrations the system becomes pseudo-first-order (PFO) dominated, consistent with transport- and ion-screening-controlled behavior. Although previous studies have provided compelling theoretical and spectroscopic evidence that interfacial electron transfer contributes to liquid–solid contact electrification in TENGs, these mechanisms have rarely been examined through such simple macroscopic kinetic formalisms. In this work, classical adsorption kinetic models are used as operational probes for distinguishing electron-transfer-influenced regimes from ion-transport-dominated regimes at PTFE/liquid interfaces. The PSO-to-PFO crossover reported here is interpreted within the hybrid EDL framework as a kinetic marker of a transition from an electron-transfer-influenced charging regime at low concentration to an ion-transport- and screening-dominated regime at high concentration, thereby demonstrating how adsorption kinetics can serve as a practical diagnostic language for liquid–solid triboelectric systems.
Keywords: Adsorption kinetic models; Electric double layer (EDL); Hybrid EDL model; Liquid-solid contact electrification; Liquid-solid interface